2021
DOI: 10.5194/amt-14-2543-2021
|View full text |Cite
|
Sign up to set email alerts
|

Airborne measurements of oxygen concentration from the surface to the lower stratosphere and pole to pole

Abstract: Abstract. We have developed in situ and flask sampling systems for airborne measurements of variations in the O2/N2 ratio at the part per million level. We have deployed these instruments on a series of aircraft campaigns to measure the distribution of atmospheric O2 from 0–14 km and 87∘ N to 86∘ S throughout the seasonal cycle. The National Center for Atmospheric Research (NCAR) airborne oxygen instrument (AO2) uses a vacuum ultraviolet (VUV) absorption detector for O2 and also includes an infrared CO2 sensor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Regional data deficiencies make isolation of the potential drivers very difficult (Mathis et al 2010;Gregg et al 2014;Roden et al 2016;Bushinksy et al 2017;Hammond et al 2017;Rosso et al 2017;Frey et al 2018;Bai et al 2019). Satellite, aircraft and float observations of some key variables (such as plankton density, sea ice algal productivity, oxygen and carbon dioxide fluxes) are as yet very sparse in high latitudes (Rysgaard et al 2011;Liang et al 2017;Gray et al 2018;Bushinsky et al 2017Bushinsky et al , 2019Pinkerton & Hayward 2021;Stephens et al 2021) and remote sensing may not quantify under-ice productivity (Tremblay et al 2012).…”
Section: Figs A11 and A12 Appendix 1)mentioning
confidence: 99%
“…Regional data deficiencies make isolation of the potential drivers very difficult (Mathis et al 2010;Gregg et al 2014;Roden et al 2016;Bushinksy et al 2017;Hammond et al 2017;Rosso et al 2017;Frey et al 2018;Bai et al 2019). Satellite, aircraft and float observations of some key variables (such as plankton density, sea ice algal productivity, oxygen and carbon dioxide fluxes) are as yet very sparse in high latitudes (Rysgaard et al 2011;Liang et al 2017;Gray et al 2018;Bushinsky et al 2017Bushinsky et al , 2019Pinkerton & Hayward 2021;Stephens et al 2021) and remote sensing may not quantify under-ice productivity (Tremblay et al 2012).…”
Section: Figs A11 and A12 Appendix 1)mentioning
confidence: 99%
“…Aircraft observations of the O2/N2 ratio have been conducted in the past (e.g. Sturm et al, 2005;Ishidoya et al, 2008aIshidoya et al, , 2012van der Laan et al, 2014;Morgan et al, 2019;Birner et al, 2020;Stephens et al, 2018Stephens et al, , 2021. Sturm et al (2005) observed a vertical gradient and seasonal cycle in the O2/N2 ratio in the height range of 0.8-3.1 km over Perthshire, United Kingdom, for the period [2003][2004].…”
mentioning
confidence: 99%
“…Kawamura et al, 2006;Ishidoya et al, 2013), however Ishidoya et al (2012) and van der Laan et al (2014) did not observe them. and Stephens et al (2021) observed O2/N2 and Ar/N2 simultaneously, and were able to correct for thermally-diffusive artificial fractionation on O2/N2, by using coefficients of 3.54 and 3.77 of Ar/O2, respectively. By using the corrected O2/N2 ratio, were able to observe spatiotemporal variations in the O2/N2 ratio from the surface to the middle troposphere over the Western North Pacific around Japan, on monthly scheduled flights, for the period May 2012 to April 2013.…”
mentioning
confidence: 99%
See 2 more Smart Citations